Quality of reporting of outcomes in trials of therapeutic interventions for pressure ulcers in adults: a protocol for a systematic survey - Miranda, Jessica Steffany [UNESP]; Fernandes Abbade, Luciana Patricia [UNESP]; Deonizio, Arthur Pollo [UNESP]; Abbade, Joelcio Francisco [UNESP]; Mbuagbaw, Lawrence; Thabane, Lehana (Bmj Publishing Group, 2019)
Pressure ulcers (PUs) have a high incidence, especially in hospital units. Randomised clinical trials (RCTs) of therapeutic interventions for PU should include a clear description of the outcomes and results to enhance transparency and replicability. Objectives The primary objective of this study is to assess the completeness of the descriptions of the outcomes of therapeutic interventions in RCTs in adult patients with PU. The secondary objectives are to evaluate the types of reported primary outcomes, measurement methods or tools used to evaluate the outcomes and the results of reported outcomes. Methods We will conduct a systematic survey of RCTs published from January 2006 to April 2018. The selection process of the studies will be done in two stages of screening: title and abstract, and full text revision, always by two researchers independently. The completeness of the outcome will be assessed according to five criteria: domain (outcome title), specific measurement or technique/ instrument used, specific metric or format of the outcome data that will be used for analysis, method of aggregation (how data from each group will be summarised) and time-points that will be used for analysis. The quality of the results of the outcome will be classified as either complete, incomplete or unreported. We will conduct a descriptive analysis of the number, type and degrees of outcome specification in the included RCTs. The frequency of categories in each domain of the outcomes will also be reported. The median and IQR will be estimated for each element of the specified outcome (out of five). Ethics and dissemination This will be the first systematic assessment of the outcomes of therapeutic interventions used for pressure ulcers. After completion, this review will be submitted to a peer-reviewed journals.